Sistem Informasi MSDM Menggunakan Microsoft Access dan OneDrive pada Politeknik LP3I Kampus Depok - Sutan Mohammad Arif; Hendro Purwoko (Universitas Indraprasta PGRI Jakarta, 2017)
Microsoft Access is a reliable database application and part of Microsoft Office application installation so that easy to be used in shorting the human resources of Politeknik LP3I Jakarta Kampus Depok. Currently, Management Information System of Human Resource on this campus, having an online system. However, the data information is less complete so that researcher try to make a cheap system by using